2014
DOI: 10.1158/1535-7163.mct-13-1043
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt Reverses the Acquired Resistance to Sorafenib by Switching Protective Autophagy to Autophagic Cell Death in Hepatocellular Carcinoma

Abstract: Sorafenib is the standard first-line systemic drug for advanced hepatocellular carcinoma (HCC), but the acquired resistance to sorafenib results in limited benefits. Activation of Akt is thought to be responsible for mediating the acquired resistance to sorafenib. The present study aims to examine the underlying mechanism and seek potential strategies to reverse this resistance. Two sorafenib-resistant HCC cell lines, which had been established from human HCC HepG2 and Huh7 cells, were refractory to sorafenib-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
234
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 238 publications
(247 citation statements)
references
References 48 publications
12
234
0
Order By: Relevance
“…Additionally, previous studies revealed that stress activates the Akt signal transduction pathway in tumor cells, which results in protective autophagy (28). Furthermore, treatment with an Akt inhibitor changed the role of autophagy from protective to lethal (27). These findings suggest that Akt signaling and autophagy are important in the resistance of tumors to treatment.…”
Section: E C D B Amentioning
confidence: 77%
See 3 more Smart Citations
“…Additionally, previous studies revealed that stress activates the Akt signal transduction pathway in tumor cells, which results in protective autophagy (28). Furthermore, treatment with an Akt inhibitor changed the role of autophagy from protective to lethal (27). These findings suggest that Akt signaling and autophagy are important in the resistance of tumors to treatment.…”
Section: E C D B Amentioning
confidence: 77%
“…Akt may be the main mechanism of autophagic cell death, since the ectopic overexpression of Akt partly rescues cancer cells from death when they are stressed (8). Additionally, previous studies have demonstrated that stress activated the Akt signal transduction pathway in tumor cells and induced protective autophagy, whereas the inhibition of the Akt signaling pathway synergistically killed cancer cells (27). In the present study, the addition of ubenimex or an Akt inhibitor significantly induced autophagic cell death, whereas an Akt agonist reduced this effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An immunoblotting assay was performed as previously described (16,17). Briefly, the cells were lysed and protein concentrations were quantified.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%